Living Belief and Cultural Values: Samin Community Participation in Geopark Development - Gunawan Hadi Purwanto; M Yasir; M Hilal Bilhaq (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study examines the integration of Samin cultural heritage within the development of the Bojonegoro Geopark, with particular attention to its representation in geopark planning, educational functions, and community participation. The research examines the integration of Samin cultural values, historical narratives, and social practices into the geopark framework. It also analyzes the forms and extent of Samin community participation in geopark-related initiatives and identifies the challenges of maintaining cultural identity within tourism-oriented development. The research employs a qualitative methodology that draws on empirical, historical, and conceptual approaches. Data were collected through in-depth interviews with Samin elders, community leaders, village officials, and members of Samin communities. Document analysis was used to examine policy documents, cultural records, and geopark planning materials. The data were analyzed using thematic analysis to identify recurring patterns, meanings, and relationships relevant to cultural representation and participation. The findings indicate that Samin's teachings emphasize honesty, non-violence, social responsibility, religious devotion, and harmony with nature. These values function as living traditions that support the educational, conservation, and community empowerment pillars of UNESCO Global Geoparks. The study also reveals active community participation in cultural preservation through rituals, traditional architecture, and cultural products. However, challenges emerge in balancing cultural authenticity with tourism-driven economic interests. The study concludes that inclusive governance and culturally sensitive geopark management are essential to ensure sustainable heritage preservation and community-centered development.